“Los recursos didácticos en el proceso de enseñanza intercultural en el área de lengua y literatura en el quinto año paralelo “D” de la unidad educativa “Belisario Quevedo” del cantón Pujilí en el año lectivo 2022-2023” - Alajo Chugchilán, Patricia Alexandra (2023)
The present research project carried out in the Educational Unit "Belisario Quevedo" of Pujili Canton in the school year 2022-2023, has detected that there is a problem regarding the teaching of interculturality in the area of Language and Literature. Hence the importance of this research, since it intends that the teacher knows the use of teaching resources. With the aim to diversify the educational process in terms of interculturality. For this reason, a qualitative methodological approach was applied, through the application of an observation guide to the teacher directly, in which it was possible to detect that there is a lack in the application of didactic resources. That is why, with the results obtained, some didactic resources were selected from different activities that tend to strengthen cultural teaching so that learning is fruitful. Therefore, each activity proposed is focused on cultural aspects starting with the identity of each student that allows them to reach to a critical reflection based on the acceptance, recognition, and valuation of their roots. Therefore, the proposal proposed can be taken to the classroom to apply favorably and build meaningful learning. In this sense, the didactic guide has been valued by university professors who have positively approved this topic, so this proposal has support, is viable, and is feasible.